2009
DOI: 10.1021/pr900042e
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Phosphorylated Proteins of Escherichia coli Ribosomes

Abstract: Phosphorylation of bacterial ribosomal proteins has been known for decades; however, there is still very limited information available on specific locations of the phosphorylation sites in ribosomal proteins and the role they might play in protein synthesis. In this study, we have mapped the specific phosphorylation sites in twenty-four E. coli ribosomal proteins by tandem mass spectrometry. Specific detection of phosphorylation was achieved by either phosphorylation specific visualization techniques, ProQ sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 72 publications
2
45
0
Order By: Relevance
“…The pieces were processed by performing in-gel tryptic digestion using methods previously established in our laboratory (Miller et al, 2008, 2009; Soung et al, 2009). Tryptic digests were analyzed by capillary liquid chromatography-nanoelectrospray ionization-tandem mass spectrometry (capLC-MS/MS).…”
Section: Methodsmentioning
confidence: 99%
“…The pieces were processed by performing in-gel tryptic digestion using methods previously established in our laboratory (Miller et al, 2008, 2009; Soung et al, 2009). Tryptic digests were analyzed by capillary liquid chromatography-nanoelectrospray ionization-tandem mass spectrometry (capLC-MS/MS).…”
Section: Methodsmentioning
confidence: 99%
“…Upon examination of BYmediated protein phosphorylation sites, no clear-cut recognition motifs emerged in the immediate surroundings of the phosphorylated tyrosines. Moreover, if one considers the number of tyrosine-phosphorylation sites detected in recent phosphoproteomic studies (table 1), the conservation of phosphotyrosine sites is nearly non-existent [84,[91][92][93][94][95][96][97][98][99]. The existence of a specific phosphorylation motif is therefore unlikely in proteins phosphorylated by BY-kinases, and it seems likely that they recognize structural motifs distant from the phosphorylated tyrosine.…”
Section: Future Prospects and Challengesmentioning
confidence: 99%
“…Whereas a number have been identified and discussed above, it is likely that there are a large number of additional targets. In recent times, phosphoproteomic studies carried out across a range of bacterial species have led to the discovery of a range of proteins phosphorylated on serine, threonine, and tyrosine (56,59,94,101). Whereas those phosphorylated on tyrosine constituted the smallest group, this is due, in part, to the fact that the methods used in these studies favor identification of more heavily phosphorylated amino acids, with tyrosine normally phosphorylated at low percentages.…”
Section: Lmw Ptp Etp Is Tyrosine Phosphorylatedwhat About Other Ptps?mentioning
confidence: 99%
“…Indeed, increased identification of PY has already been evident in investigations of E. coli. Whereas a phosphoproteomic analysis of the whole cell led to the identification of only seven tyrosines phosphorylated (55), a more defined study of only ribosomal-binding proteins found that 11 of these proteins were tyrosine phosphorylated (94). Furthermore, a recent study utilizing methods to solely investigate the tyrosine phosphoproteome of E. coli found a total of 342 tyrosine phosphorylated proteins (38).…”
Section: Fig 9 Possible Mechanisms For Role Of Ptps In Cpsmentioning
confidence: 99%